Análise multicriterial como ferramenta para a AAE da Bacia Hidrográfica do Rio Grande, vertente mineira - Ávila, Patrícia Andressa (2016)
Strategic Environmental Assessment (SEA) is the term used to describe the process of environmental assessment of policies, plans or programs that should be approved before the individual projects authorization. The Brazilian territory has a comfortable situation in relation to the availability of water. However, this resource is badlydistributed in relation to the demography of the country. Considering the important and the necessity of water preservation, it is necessary recuperate the quality and quantity of water resources, suggesting that significant interferences in the watersheds should pass through SEA process. In this context, this work aimed to investigate the relevance of using the SEA in the Rio Grande watershed, Minas Gerais State, through the multicriteria analysis. It was used multicriteria analisys, which the factors soil classes, soil use, water quality index and economic ecologic index were standardized and reclassified. Using the Analytic Hierarchy Process technique (ArcGIS 10.3) and the weighting scale Saaty, the factors received weights based on the importance among them to the preservation of Rio Grande watershed. It is possible to notice by the applied methodology that more than 50% of the area studied were in a situation considered good. The GD1, GD2 e GD3 units did not show representative values in area percentage to the preservation class very good. The area of this study has 34.51% as classification of preservation considered medium, which shows that exist the necessity of creating effective measures to the conservation of the watershed. In this context, through the analysis of technical, legal, governance and social considerations, it is possible to conclude that SEA could collaborate positively to the conservation and preservation of the Rio Grande watershed.